Fresh Graduates’ Perseptions Of The TikTok Content ‘Marriage is Scary’ - Putri, Agustia Rinjani; Damaiyanti, Varinia Pura (The Future of Education Journal, 2026)
This study aims to examine how fresh graduates perceive marriage after watching Marriage is Scary content and how the discourse within the content constructs fear of marriage. This research employs a qualitative approach using discourse analysis. The subjects of this study are fresh graduates in Banjarmasin City who have watched the Marriage is Scary content. Data were collected through in-depth interviews and analyzed using Michel Foucault’s perspective, which views discourse as power relations that produce knowledge and shape how individuals understand reality. The findings reveal that Marriage is Scary content does not merely present personal experiences but also reproduces particular discourses about marriage. These discourses shape fresh graduates’ perceptions through narratives of domestic conflict, gender role inequality, emotional burdens, and fear of physical and personal changes after marriage. The fear of marriage that emerges is not natural or inherent; rather, it is constructed through power relations embedded in social media discourse. Therefore, this study concludes that the discourse within TikTok content Marriage is Scary plays a significant role in shaping fresh graduates’ perceptions of marriage.